2010
DOI: 10.1111/j.1523-1739.2010.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Maladaptive Attractiveness of Solar Panels to Polarotactic Insects

Abstract: Human-made objects (e.g., buildings with glass surfaces) can reflect horizontally polarized light so strongly that they appear to aquatic insects to be bodies of water. Insects that lay eggs in water are especially attracted to such structures because these insects use horizontal polarization of light off bodies of water to find egg-laying sites. Thus, these sources of polarized light can become ecological traps associated with reproductive failure and mortality in organisms that are attracted to them and by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
88
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 35 publications
(43 reference statements)
0
88
0
6
Order By: Relevance
“…asphalt roads, oil lakes, black plastic sheets used in agriculture, shiny dark-coloured cars, solar panels and collectors) -mimicking the reflection-polarization characteristics of water surfaces -may confuse flying, water-seeking polarotactic water insects. These man-made polarizing reflecting surfaces cause daylong polarized light pollution, that has disastrous consequences for polarotactic insects (Horváth and Zeil 1996;Kriska et al 2006;Bernáth et al 2001;Horváth et al 2009Horváth et al , 2010a.…”
Section: Introductionmentioning
confidence: 99%
“…asphalt roads, oil lakes, black plastic sheets used in agriculture, shiny dark-coloured cars, solar panels and collectors) -mimicking the reflection-polarization characteristics of water surfaces -may confuse flying, water-seeking polarotactic water insects. These man-made polarizing reflecting surfaces cause daylong polarized light pollution, that has disastrous consequences for polarotactic insects (Horváth and Zeil 1996;Kriska et al 2006;Bernáth et al 2001;Horváth et al 2009Horváth et al , 2010a.…”
Section: Introductionmentioning
confidence: 99%
“…3, Supporting Fig. S2 Horváth et al 2010aHorváth et al , 2011 suggest that ARC's were not sufficiently effective to 380 reduce chironomid attraction. 381…”
mentioning
confidence: 99%
“…Moreover, vertical artificial polarizers are just as effective at triggering maladaptive 398 behavior as horizontal ones (Kriska et al 2008) and so the orientation of panels at angles perpendicular 399 to the direction of the mid-day sun is not likely to either mitigate or exacerbate the patterns we have 400 seen here. Previous research has shown that one solution to this problem is to manufacture PV panels 401 with a dense grid of thin white lines (Horváth et al 2010a Because polarized light pollution triggers severely maladaptive behavior in nearly every single 407…”
mentioning
confidence: 99%
See 2 more Smart Citations